Upaya Mahasiswa PPL untuk Meningkatkan Pemahaman Belajar Siswa Melalui Metode Demonstrasi di SPM Aliyah Mustahafawiyah Purba Baru - Syafii, Rahmad; Hasibuan, Suci Permadani; Madinah, Shelly; Banun, Siti; Adawiyah, Rabiatul; Siregar, Listi hani (Faidatuna, 2024)
The teaching and learning process is the core of the overall educational process, the teacher plays the main role. One part of the learning planning component is the method. A method is a method used to achieve a predetermined goal. The demonstration method is a teaching method that uses demonstration to clarify an understanding of paying attention to doing something to students. In the learning process, solutions will also arise. Application of the demonstration method in learning fiqh, moral beliefs, al-Qur'an hadith, Arabic language, and counseling guidance. Based on the results of research regarding problems in the application of learning, it can be concluded that: students do not understand enough about the subjects they are taking because they do not include examples or provide an overview of the discussion being discussed. The solution used to overcome problems in the application of learning, the demonstration method will overcome students' problems is to provide guidance in the form of direction and motivation using the demonstration method which we will apply so that it is easier to understand as the learning process continues.